RADITION OF MERISIK AND PRACTICE OF RESTRICTING THE SOCIAL MEDIA OF YOUNG PEOPLE IN BANDAR SONO VILLAGE, BATU BARA DISTRICT - Ariani, Devi (FORUM PAEDAGOGIK, 2025)
This study aims to explore the practice of the merisik tradition within the Malay community of Bandar Sono Village, Batu Bara Regency, and how this tradition plays a role in shaping social boundaries for young people. The method used is a qualitative approach with data collected through in-depth interviews with traditional leaders, religious figures, the village head, couples who have experienced the merisik tradition, parents from both families, and members of the local community. The findings indicate that the merisik tradition is still actively practiced and not only serves as an initial stage before engagement, but also represents a form of respect toward the woman's family and an effort to preserve the honor of both parties. This tradition plays an important role in maintaining social order, particularly in regulating interactions between young men and women to align with cultural norms and Islamic teachings. It carries educational values such as responsibility, respect for parents, modesty, religious values, appreciation for tradition, and the regulation of interactions between males and females. Therefore, the merisik tradition remains relevant today as a form of character education rooted in local cultural values.